High‐Efficiency, Solution‐Processed White Quantum Dot Light‐Emitting Diodes with Serially Stacked Red/Green/Blue Units. Issue 20 (1st August 2018) - Cao, Fan; Zhao, Dewei; Shen, Piaoyang; Wu, Jialong; Wang, Haoran; Wu, Qianqian; Wang, Feijiu; Yang, Xuyong
Abstract: Despite the fast advances in monochrome quantum dots (QDs) based light‐emitting diodes (QLEDs), the performance for white QLEDs (WQLEDs) with great potential for illumination and backlight applications to date has fallen short of that of state‐of‐the‐art white organic LEDs. Here, a highly efficient all‐solution‐processed WQLED with a serially stacked red/green/blue tandem structure, which displays an almost perfect white emission with the Commission Internationale de l'Enclairage coordinates of (0.34, 0.33) is reported. The white device exhibits peak current efficiency of 79.9 cd A −1 and external quantum efficiency of 28.0%, which are the highest efficiency values ever reported in WQLEDs. The record performance for the WQLEDs is achieved by the effective interconnecting layer with excellent charge generation and the insertion of a polyethylenimine ethoxylated interlayer between the ZnO electron transport layer and QDs emissive layer in each unit for better balancing charge injection and suppressing the quenching of QDs emission due to the contact with ZnO. Abstract : A highly efficient white quantum dot light‐emitting diode with a serially stacked red/green/blue tandem structure connected by an effective interconnecting layer is reported. The best‐performing device displays an almost perfect white emission, with a maximum current efficiency and external quantum efficiency of 79.9 cd A −1 and 28.0%, respectively, which are the highest values ever reported.